Near miss [compact disc, unabridged] - Woods, Stuart; Battles, Brett (Woods, Stuart. Stone Barrington novel., 2023)
Following a string of adventures, Stone Barrington is enjoying some downtime in New York City when a chance encounter introduces him to a charming new companion. Too bad she also comes with the baggage of a persistent ex-boyfriend intent on retribution. As Stone skillfully dodges each disturbance, it becomes clear that there's an even more treacherous game being played behind the scenes. When long-standing grudges resurface, Stone is brought back into the orbit of some familiar enemies. He must use all of his tricks, as well as those of a few old friends, to evade trouble before it's too late. But this time, danger just might catch up with him.